Adaptation of the socioecological model to address disparities in engagement of Black men in prostate cancer genetic testing - Amy E. Leader; Timothy R. Rebbeck; William K. Oh; Alpa V. Patel; Eric P. Winer; LeeAnn O. Bailey; Leonard G. Gomella; Crystal Y. Lumpkins; Isla P. Garraway; Lisa B. Aiello; Monica L. Baskin; Heather H. Cheng; et al. (BMC, 2024)
Abstract Background Black men consistently have higher rates of prostate cancer (PCA)- related mortality. Advances in PCA treatment, screening, and hereditary cancer assessment center around germline testing (GT). Of concern is the significant under-engagement of Black males in PCA GT, limiting the benefit of precision therapy and tailored cancer screening despite longstanding awareness of these disparities. To address these critical disparities, the Socioecological Model (SEM) was employed to develop comprehensive recommendations to overcome barriers and implement equitable strategies to engage Black males in PCA GT. Methods Clinical/research experts, national organization leaders, and community stakeholders spanning multiple regions in US and Africa participated in developing a framework for equity in PCA GT grounded in the SEM. A novel mixed-methods approach was employed to generate key areas to be addressed and informed statements for consensus consideration utilizing the modified Delphi model. Statements achieving strong consensus (> =75% agreement) were included in final equity frameworks addressing clinical/community engagement and research engagement. Results All societal levels of the SEM (interpersonal, institutional, community, and policy/advocacy) must deliver information about PCA GT to Black males that address benefits/limitations, clinical impact, hereditary cancer implications, with acknowledgment of mistrust (mean scores [MS] 4.57-5.00). Interpersonal strategies for information delivery included engagement of family/friends/peers/Black role models to improve education/awareness and overcome mistrust (MS 4.65-5.00). Institutional strategies included diversifying clinical, research, and educational programs and integrating community liaisons into healthcare institutions (MS 4.57-5.00). Community strategies included partnerships with healthcare institutions and visibility of healthcare providers/researchers at community events (MS 4.65-4.91). Policy/advocacy included improving partnerships between advocacy and healthcare/community organizations while protecting patient benefits (MS 4.57-5.00). Media strategies were endorsed for the first time at every level (MS 4.56-5.00). Conclusion The SEM-based equity frameworks proposed provide the first multidisciplinary strategies dedicated to increase engagement of Black males in PCA GT, which are critical to reduce disparities in PCA-mortality through informing tailored screening, targeted therapy, and cascade testing in families.